1993
DOI: 10.1037/0735-7044.107.4.539
|View full text |Cite
|
Sign up to set email alerts
|

Rapid development of learning-induced receptive field plasticity in the auditory cortex.

Abstract: Classical conditioning induces frequency-specific receptive field (RF) plasticity in the auditory cortex after relatively brief training (30 trials), characterized by increased response to the frequency of the conditioned stimulus (CS) and decreased responses to other frequencies, including the pretraining best frequency (BF). This experiment determined the development of this CS-specific RF plasticity. Guinea pigs underwent classical conditioning to a tonal frequency, and receptive fields of neurons in the au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
131
3

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 201 publications
(149 citation statements)
references
References 28 publications
(61 reference statements)
15
131
3
Order By: Relevance
“…Systemic administration of scopolamine to healthy humans induces impairment to attentional processes, and memory, as well as decreases in higher frequency gamma/beta EEG power relative to lower frequency delta/theta power (Ebert and Kirch, 1998). Although not directly demonstrated in the current study, VNS has been shown to excite the nucleus basalis (NB) (Detari et al, 1983) and similarly to VNS, NB activation promotes arousal, suppresses seizure activity Berdiev et al, 2007), and promotes neural plasticity (Edeline et al, 1993;Engineer et al, 2011). The suppression of evoked responses to repetitive stimuli by brief activation of VNS we demonstrate are notably similar to the suppression induced by arousal (Castro-Alamancos and Connors, 1996b); however, their precise relationship remains unknown.…”
Section: Discussionmentioning
confidence: 86%
“…Systemic administration of scopolamine to healthy humans induces impairment to attentional processes, and memory, as well as decreases in higher frequency gamma/beta EEG power relative to lower frequency delta/theta power (Ebert and Kirch, 1998). Although not directly demonstrated in the current study, VNS has been shown to excite the nucleus basalis (NB) (Detari et al, 1983) and similarly to VNS, NB activation promotes arousal, suppresses seizure activity Berdiev et al, 2007), and promotes neural plasticity (Edeline et al, 1993;Engineer et al, 2011). The suppression of evoked responses to repetitive stimuli by brief activation of VNS we demonstrate are notably similar to the suppression induced by arousal (Castro-Alamancos and Connors, 1996b); however, their precise relationship remains unknown.…”
Section: Discussionmentioning
confidence: 86%
“…MGv plasticity is more consistent with Suga's model of time-limited subcortical auditory plasticity. However, incompatible with the Suga view of slowly developing cortical plasticity is the fact that RF plasticity in A1 develops rapidly, within only five training trials 18 .…”
Section: Loci Of Plasticitymentioning
confidence: 89%
“…RF plasticity was still present after one hour. The opposite changes in response to the CS frequency and the pre-training BF could be very large and even produce a reversal of response sign, that is, a CS frequency that was originally inhibitory became excitatory and vice versa for the pre-training BF 18 (Fig. 2a).…”
Section: Receptive Field Plasticity: Tuning Shiftsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, changes in the responses of auditory cortex neurons are already observed after 5 conditioning trials and reach its maximum after 15 trials (Edeline, Pham, & Weinberger, 1993). Moreover, different neuron populations show plastic changes with different temporal properties, with units showing alterations in the early phase of learning and others whose modification has a slower course ).…”
Section: Fear Conditioning Induces Plastic Changes In Neuronal Responmentioning
confidence: 99%